Shiny-phyloseq: Web application for interactive microbiome analysis with provenance tracking - Paul J. McMurdie; Susan Holmes (2014)
Abstract Summary: We have created a Shiny-based Web application, called Shiny-phyloseq , for dynamic interaction with microbiome data that runs on any modern Web browser and requires no programming, increasing the accessibility and decreasing the entrance requirement to using phyloseq and related R tools. Along with a data- and context-aware dynamic interface for exploring the effects of parameter and method choices, Shiny-phyloseq also records the complete user input and subsequent graphical results of a user’s session, allowing the user to archive, share and reproduce the sequence of steps that created their result—without writing any new code themselves. Availability and implementation : Shiny-phyloseq is implemented entirely in the R language. It can be hosted/launched by any system with R installed, including Windows, Mac OS and most Linux distributions. Information technology administrators can also host Shiny-phyloseq from a remote server, in which case users need only have a Web browser installed. Shiny-phyloseq is provided free of charge under a GPL-3 open-source license through GitHub at http://joey711.github.io/shiny-phyloseq/ . Contact : mcmurdie@alumni.stanford.edu .